2022
DOI: 10.3389/fpsyg.2022.876990
|View full text |Cite
|
Sign up to set email alerts
|

From ivory tower to inclusion: Stakeholders’ experiences of community engagement in Australian autism research

Abstract: Autistic people, and other community stakeholders, are gaining increasing recognition as valuable contributors to autism research, resulting in a growing corpus of participatory autism research. Yet, we know little about the ways in which stakeholders practice and experience community engagement in autism research. In this study, we interviewed 20 stakeholders (academics, autistic people, family members/careers, research students, and service providers) regarding their experiences of community engagement in Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 42 publications
(64 reference statements)
1
9
0
Order By: Relevance
“…The sub-theme “Gaining insight into the ivory tower” revealed a prevailing tendency to rely on the assumptions of key opinion leaders instead of the perspectives and experiences of patients. This was also observed in literature (6, 15, 17, 28). Many stakeholders, in particular patient representatives and clinical researchers, reflected on their respective roles in clinical research.…”
Section: Discussionsupporting
confidence: 90%
“…The sub-theme “Gaining insight into the ivory tower” revealed a prevailing tendency to rely on the assumptions of key opinion leaders instead of the perspectives and experiences of patients. This was also observed in literature (6, 15, 17, 28). Many stakeholders, in particular patient representatives and clinical researchers, reflected on their respective roles in clinical research.…”
Section: Discussionsupporting
confidence: 90%
“…As such, we have little knowledge on the actual process of conducting participatory research, even though respecting and evaluating the impact of co-produced research is a key aspect of the participatory research process (Hickey et al, 2018). Those few existing studies that have evaluated the participatory process after the research was concluded (den Houting et al, 2021, 2022; Jose et al, 2020) have found that, while stakeholders were broadly positive about their experiences, they remained unclear about their roles/responsibilities and found power imbalances between researchers and community members challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Genuinely inclusive, participatory research tends to be more socially just, innovative, accessible, and reflective of participants' lived experiences than research undertaken without a similar degree of power‐sharing (McDonald, 2017). Although inclusive, coproduced and participatory methodologies are typically employed in only a minority of autism research studies, there is a growing demand from the autistic community to be involved in the research process (den Houting et al, 2021, 2022; Dwyer et al, 2021; Pukki et al, 2022; Stark, 2022), resulting in a shift of the direction of much research to focus on the priorities of autistic people and their allies (Fletcher‐Watson et al, 2019; Keating, 2021; Poulsen et al, 2022); family members in particular can be important allies to include in many participatory projects (Fletcher‐Watson et al, 2019). Results are similarly positive when participatory studies of autism are evaluated by participants (Pellicano et al, 2022).…”
mentioning
confidence: 99%
“…To this end, the research community increasingly seeks to embrace this participatory approach but has outlined barriers enabling participatory research, including communication disparities between researchers and collaborators, systems‐level factors that disincentivize participatory methods, and limited avenues that enable involvement of the community within academic research (den Houting et al, 2021, 2022; Hollin & Pearce, 2019; Milton et al, 2019; Nicolaidis et al, 2019; Pellicano et al, 2014; Pickard et al, 2022). Considerable time commitment and increased funding requirements represent additional oft‐cited barriers that prevent researchers from adopting participatory research practices (den Houting et al, 2021; Drahota et al, 2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation